Inflammatory expression profile in peripheral blood mononuclear cells from patients with Nasu-Hakola Disease. (April 2019) - Galimberti, D.; Fenoglio, C.; Ghezzi, L.; Serpente, M.; Arcaro, M.; D'Anca, M.; De Riz, M.; Arighi, A.; Fumagalli, G.G.; Pietroboni, A.M.; Piccio, L.; Scarpini, E.
Highlights: BMP-1 and TGFB3 mRNA levels were increased in PBMC from NHD versus controls. CXCL5, PPBP and PF4V1 were downregulated in PBMC from NHD versus controls. IL-15 and TNFSF4 mRNA levels were mildly decreased in NHD versus controls. No significant differences were observed in heterozygosis, apart from IL-15. We identified an inflammatory signature of NHD patients. Abstract: Homozygous mutations in Triggering Receptor Expressed on Myeloid cells 2 gene ( TREM2 ) are one of the major causes of Nasu Hakola Disease (NHD). We analysed Peripheral Blood Mononuclear Cells (PBMC) profile of 164 inflammatory factors in patients with NHD carrying the TREM2 Q33X mutation as compared with heterozygous and wild type individuals. Several molecules related to bone formation and angiogenesis were altered in NHD compared to non-carriers: Bone Morphogenetic Protein (BMP)-1 mRNA levels were significantly increased in PBMC (2.32 fold-increase; P  = 0.01), as were Transforming Growth Factor Beta (TGFB)3 levels (1.51 fold-increase; P  = 0.02). Conversely, CXCL5 and Pro Platelet Basic Protein (PPBP) were strongly downregulated (−28.26, −9.85 fold-decrease over non-carriers, respectively, P  = 0.01), as well as Platelet Factor 4 Variant 1 (PF4V1; −41.44, P  = 0.03). Among other inflammatory factors evaluated, Interleukin (IL)-15 and Tumor Necrosis Factor Superfamily Member (TNFSF)4 mRNA levels were decreased in NHD as compared with non-carriers (−2.25 and −3.87 fold-decrease, P  = 0.01 and 0.001, respectively). In heterozygous individuals, no significant differences were observed, apart from IL-15 mRNA levels, that were decreased at the same extent as NHD (−2.05 fold-decrease over non-carriers, P  = 0.002). We identified a signature in PBMC from patients with NHD consisting of strongly decreased mRNA levels of CXCL5, PPBP, PF4V1, mildly decreased IL-15 and TNFSF4 and mildly increased BMP-1 and TGFB3.